Shedding New Light on the Pure Copper Metallurgy of the Chalcolithic Southern Levant Through an Archaeological Experiment - Thomas Rose; Peter Fabian; Yuval Goren (EXARC Journal, 2021)
Two metallurgical traditions coexisted in the Chalcolithic Southern Levant: the lost wax casting of polymetallic alloys and the pure copper technology. Details of their operational sequences are still unknown. To date, no production sites of lost wax casting technology have been found. Only the main steps of the pure copper technology can be reconstructed from the archaeological record. Therefore, an archaeological experiment was carried out to shed new light on both technologies. Concerning the pure copper technology, the experiment focussed on the draught technique and high-temperature behaviour of the crucible and furnace clays. Based on archaeological evidence, a furnace and crucibles were reconstructed with local clays used by ancient metallurgists. Instead of the commonly hypothesised blowpipes, bellows were used to produce the draught. The furnace was successfully operated with bellows and reached temperatures high enough to melt copper. Furthermore, the clays’ behaviour varied considerably due to high heat exposure, but they are suitable if used appropriately. Our experiment establishes this draught technique as a viable alternative to the commonly assumed blowpipes as well as the suitability of local clays.